2021
DOI: 10.3390/plants10040708
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Kinetics of Metalaxyl Accumulation and Dissipation in Durian (Durio zibethinus L.) Leaf Using High-Performance Liquid Chromatography (HPLC) Technique

Abstract: Metalaxyl is an effective approach to control Phytophthora palmivora infection in durian plantation. However, inappropriate metalaxyl usage may increase production cost, pathogen with fungicide resistance, and environmental toxicity. This study established and validated a simple and reproducible procedure to measure metalaxyl concentration in the durian leaf using HPLC. Linearity of the detection ranged from 1–100 µg/mL. The limits of detection (LOD) and quantification (LOQ) were 0.27 and 0.91 µg/mL, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Regarding the chemical classes, the dissipation half-lives of triazoles were reported to be in the range of 2–12.8 days [ 45 ], which is similar to our results and previous studies. The half-life of metalaxyl was reported to be 2.5 days in Chinese cabbage [ 46 ], 3–3.5 days in cucumber [ 47 ], 4.9 days in grape [ 37 ], and 16.5 days in durian leaf [ 48 ]. The decomposition behavior of pesticides is generally influenced by many factors such as their physicochemical characteristics, formulations, environmental conditions, crop species, and plant growth-based dilution factor [ 29 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the chemical classes, the dissipation half-lives of triazoles were reported to be in the range of 2–12.8 days [ 45 ], which is similar to our results and previous studies. The half-life of metalaxyl was reported to be 2.5 days in Chinese cabbage [ 46 ], 3–3.5 days in cucumber [ 47 ], 4.9 days in grape [ 37 ], and 16.5 days in durian leaf [ 48 ]. The decomposition behavior of pesticides is generally influenced by many factors such as their physicochemical characteristics, formulations, environmental conditions, crop species, and plant growth-based dilution factor [ 29 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Metalaxyl inhibits fungal RNA synthesis (Drenth & Guest, 2004;Torres-londono, 2016). Metalaxyl can slowly penetrate through the leaf cuticle and into the xylem of a low lipophilic host (Phetkhajone et al, 2021). After penetration, metalaxyl accumulates and is transported upward by the transpiration stream.…”
Section: Chemical Controlmentioning
confidence: 99%
“…The study also concluded that metalaxyl foliar application at 4g/L is sufficient to control P. palmivora in two months. However, a lower concentration is suggested for soil drenching to treat the root and stem rot disease in durian trees (Phetkhajone et al, 2021). Protectant fungicide, mefenoxam, is a purified active isomer of metalaxyl that can affect mycelium growth and sporulation (Schwinn & Staub, 1995;Ware & Withacre, 2004).…”
Section: Chemical Controlmentioning
confidence: 99%